Unpleasant Symptoms and Their Influences on Quality of Life in Patients with Liver Cirrhosis - Amornchevanun, Piyanat; Pongthavornkamol, Kanaungnit; Charoenkitkarn, Vishuda; Tanwandee, Tawesak (Nursing Science Journal of Thailand, 2015)
Purpose: To study the perceived unpleasant symptoms, quality of life, and the predictive power of five most distress unpleasant symptoms on quality of life in patients with liver cirrhosis. Design: Correlational predictive research. Methods: The samples included 100 patients with liver cirrhosis who came for follow up, at outpatient liver clinic of one university hospital in Bangkok. Data were collected by using: 1) a demographic questionnaire, 2) the Memorial Symptom Assessment Scale (MSAS) developed by Portenoy and colleagues, and 3) WHOQOL-BREF-THAI. Data were analyzed by using descriptive statistics and multiple regressions. Main findings: The results indicated that quality of life of patients with liver cirrhosis was at moderate level (mean score = 76.69, SD = 8.72). The top five most distress unpleasant symptoms reported by patients with liver cirrhosis were fatigue, followed by muscle cramps, anxiety, insomnia and lack of appetite. Among these symptoms: fatigue, anxiety, and insomnia were significant predictors that could explain 30.5% of the variance in QOL (R2 = .31, F = 8.27, p < .05). Fatigue was the strongest predictor of QOL (β = - .32) followed by Insomnia (β = - .22) and anxiety (β = - .19), respectively. Conclusion and recommendations: Nurses should pay attention to assess and manage unpleasant symptoms in patients, particularly fatigue, anxiety, and insomnia to improve quality of life in patients with liver cirrhosis. อาการไม่พึงประสงค์และอิทธิพลของอาการต่อคุณภาพชีวิตในผู้ป่วยโรคตับแข็ง บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาการรับรู้อาการไม่พึงประสงค์ คุณภาพชีวิต และอิทธิพลของอาการไม่พึงประสงค์ที่รบกวนมากที่สุด 5 อันดับแรกต่อคุณภาพชีวิตของผู้ป่วยโรคตับแข็ง รูปแบบการวิจัย: ความสัมพันธ์เชิงทำนาย วิธีดำเนินการวิจัย: กลุ่มตัวอย่างเป็นผู้ป่วยโรคตับแข็งที่มาติดตามการรัษาที่คลินิกโรคตับ ตึกผู้ป่วยนอกของโรงพยาบาลมหาวิทยาลัยแห่งหนึ่งในกรุงเทพฯ จำนวน 100 คน เก็บข้อมูลโดยใช้แบบสอบถาม ประกอบด้วย 1) แบบบันทึกข้อมูลส่วนบุคคล 2) แบบสอบถามการมีอาการไม่พึงประสงค์ของ Portenoy และคณะ 3) แบบประเมินคุณภาพชีวิตใช้ขององค์การอนามัยโลกชุดย่อฉบับภาษาไทย วิเคราะห์ข้อมูลโดยใช้สถิติเชิงบรรยายและวิเคราะห์อำนาจการทำนายของตัวแปรที่ศึกษาโดยใช้สถิติสัมประสิทธิ์การถดถอยพหุคูณ ผลการวิจัย: ผู้ป่วยโรคตับแข็งมีคุณภาพชีวิตโดยรวมอยู่ในระดับปานกลาง คะแนนเฉลี่ยเท่ากับ 76.69 (SD = 8.72) อาการไม่พึงประสงค์ที่ผู้ป่วยรายงานว่ารบกวนการดำเนินชีวิตประจำวันสูงที่สุด 5 อาการ ได้แก่ อาการอ่อนล้า รองลงมาได้แก่ อาการตะคริว ความกังวล/กลุ้มใจ นอนไม่หลับ/นอนหลับยาก และอาการเบื่ออาหาร ตามลำดับ ดดยมีอาการ 3 อาการ ได้แก่ อาการอ่อนล้า ความกังวลใจ/กลุ้มใจ และอาการนอนไม่หลับ/นอนหลับยาก มีอิทธิพลที่สามารถร่วมกนทำนายคุณภาพชีวิตในผู้ป่วยโรครับแข็งได้ร้อยละ 30.5 อย่างมีนัยสำคัญทางสถิติ (R2 = .31, F = 8.27, p < .05) โดยอาการอ่อนล้า มีน้ำหนักอธิบายความแปรปรวนของคุณภาพชีวิตในผู้ป่วยโรคตับแข็งได้มากที่สุด (β = - .32) รองลงมาคือ อาการนอนไม่หลับ/นอนหลับยาก (β = - .22) และความกังวล/กลุ้มใจ (β = - .189) ตามลำดับ สรุปและข้อเสนอแนะ: พยาบาลควรให้ความสนใจต่อการประเมินอาการและจัดการกับอาการไม่พึงประสงค์ในผู้ป่วยโรคตับแข็ง โดยเฉพาะอาการอ่อนล้า นอนไม่หลับ/นอนหลับยากและความกังวล/กลุ้มใจ เพื่อเพิ่มคุณภาพชีวิตของผู้ป่วยกลุ่มนี้ต่อไป คำสำคัญ: อาการไม่พึงประสงค์ คุณภาพชีวิต ผู้ป่วยโรคตับแข็ง